A Guide to the Principles of Animal Nutrition - Cherian, Gita (Open textbook library., 2020)
Based on over 20 years of teaching experience in animal nutrition, this study guide will enhance learning basic food animal nutritional principles.In this introductory text, six fundamental nutrients, their structure, digestion, and metabolism are covered. A brief introduction to bioenergetics, feed additives, nutrient analysis, digestive organs and processes in monogastric and ruminant animals, and methods for assessing nutrient utilization are also included.Each chapter is illustrated with a new terms box, key points, and review questions.This study guide is an essential learning tool for undergraduate students majoring in animal sciences, veterinary medicine, or other related disciplines.